Exploring human milk oligosaccharides: mechanisms linking gut function to cognitive development in human and pig physiology - Li, Wentian; Gunn, Allan; Zheng, Xiaoming; Ma, Jingyi; Sheng, Nan; Wang, Bing (Frontiers in Nutrition, 2025)
Human milk oligosaccharides (HMOs) are emerging as key modulators of host physiology, with growing evidence supporting their role in shaping gut microbial communities and influencing neurocognitive outcomes. This review critically examines the impact of HMOs on gut health and behavioral responses, focusing on the complex relationship between HMOs and host physiology in both human and pigs. Given their anatomical, physiological, and microbiome similarities to humans, pigs serve as a valuable translational model for investigating the functional roles of HMOs. We summarize experimental methodologies employed in HMO research and highlight findings that demonstrate HMO-induced alterations in microbial diversity, gut integrity, and cognitive performance. Potential mechanisms of action, including gut–brain axis signaling, immune modulation, and microbial metabolite production, are explored. This review concludes by identifying current knowledge gaps and proposing future research directions aimed at elucidating HMO structure–function relationships, with implications for advancing both human nutrition and animal health.